Trastuzumab-induced cardiotoxicity in early breast cancer patients: a retrospective study of possible risk and protective factors. Issue 9 (24th January 2013) - Farolfi, Alberto; Melegari, Elisabetta; Aquilina, Michele; Scarpi, Emanuela; Ibrahim, Toni; Maltoni, Roberta; Sarti, Samanta; Cecconetto, Lorenzo; Pietri, Elisabetta; Ferrario, Cristiano; Fedeli, Anna; Faedi, Marina; et al.
Abstract : Objective: Although adjuvant trastuzumab improves survival in patients with HER2-positive early breast cancer, there is growing concern about the long-term effect of trastuzumab-induced cardiotoxicity (TIC). We retrospectively assessed the incidence of TIC and heart failure (HF) to identify possible risk and protective factors. Design: Retrospective study. Setting: Institute for Cancer Research and Treatment, Medical Oncology Department. Patients: Consecutive patients who started adjuvant trastuzumab between 2007 and 2010. Main outcome: Measures TIC was defined as an absolute left ventricular ejection fraction (LVEF) decrease ≥15 points from baseline or a LVEF<50%. Logistic regression was used to estimate OR and their 95% CI in order to evaluate the risk of TIC, considering potential cardiac risk factors (hypertension, hypercholesterolaemia, diabetes mellitus, smoke, cardiac ischaemia and previous chest radiotherapy) and protective factors (β-blockers, ACE inhibitors and/or angiotensin receptor blockers). Results: Among 179 patients, 78 cases of TIC (44%, 95% CI 37% to 51%) and four cases of HF (2%, 95% CI 0% to 4%) were reported. 14 patients stopped trastuzumab as a result of TIC. None of the cardiac risk factors or concomitant cardiovascular medications altered the risk of TIC. A previous cumulative dose >240 mg/m 2 of doxorubicin or >500 mg/m 2 of epirubicin increased the risk of TIC compared with lower doses (OR 3.07; 95% CI 1.29 to 7.27, p=0.0011). Conclusions: TIC is a frequent, albeit generally mild, adverse event in clinical practice. Further studies are warranted to better define the risk of and protective factors for TIC.